ID: 25. Issue 1 (November 2015) - Lim, Ji Eun; Chung, EunKyung; Son, Youngsook
<x xml:space="preserve">Abstract</x> We recently showed that intravenous treatment of Substance P (SP) after spinal cord injury increased the number of alternatively activated M2 macrophages at injured lesion of spinal cord and eventually promoted tissue repair. However, it was unclear enhanced M2 polarization of differentiated macrophages is resulted from SP-mediated signaling pathway or accompanied by immune modulatory actions of SP. In the present study, we aim to elucidate the direct effect of SP in M2 polarization in tissue macrophages. Rat macrophages (MØ), differentiated with GM-CSF treatment for 5 days on bone marrow-derived monocytes (MO) were prepared. Immunofluorescence staining with specific marker for monocytes and macrophages, MØ was characterized as ED-1 (CD68, a marker for macrophages) and CCR7-positive M1-like precursor differentiated from CD14 and CD11b-positive bone marrow monocytes. Administration of SP in MØ enhanced the expression of M2 marker, CD206 and CD163 concurrently with the reduction of M1 marker, CCR7 and CD68. M2 polarization of MØ in response to SP was completely blocked by NK1-R antagonist, RP67580, and PI3K inhibitor, LY294002. Furthermore, SP also showed transforming ability of M1-polarized MØ induced by IFN toward M2 type with induction of CD163 expression. In summary, the results of the present study demonstrate that SP directly polarizes M2 macrophages of MØ and IFN-primed M1 type and acts as a Th2 cytokine.